Replication-Defective Adenovirus Infection Reduces Helicobacter felis Colonization in the Mouse in a Gamma Interferon- and Interleukin-12-Dependent Manner - Jiang, Bo (American Society for Microbiology (ASM), 1999)
Helicobacter infection leads to chronic inflammation of the stomach. Although the infection persists in spite of an immune response, animal studies have shown that adjuvant-based oral vaccines can protect against infection and even eliminate established infection. These vaccines are thought to induce a Th2 immune response, counterbalancing the Th1 response seen with natural infections. As a prelude to using adenovirus vectors carrying cytokine genes to modulate the immune response to established Helicobacter felis infection, we first examined the effect of the replication-defective adenovirus (RDA) vector itself. C57BL/6 mice chronically infected with H. felis (8 to 10 weeks) received intramuscular injections of RDA. The effect of RDA on the severity of H. felis colonization and the degree of gastric inflammation was assessed 2 weeks later. RDA caused a significant decrease in H. felis colonization without significantly altering the associated inflammation. RDA did not alter the H. felis-specific immunoglobulin G1 (IgG1), IgG2a, and IgA responses in the serum but was associated with an increase in gamma interferon (IFN-γ)-producing CD8(+) spleen cells. To determine if IFN-γ or Th1 cytokines were involved in the response to RDA, we examined RDA treatment of H. felis infection in mice lacking either IFN-γ or interleukin-12 (IL-12). RDA failed to alter H. felis colonization in either of these two mouse strains. Thus, viral infection of mice chronically infected with H. felis led to a significant decrease in H. felis colonization in an IFN-γ- and IL-12-dependent manner. These results demonstrate that Th1 responses associated with systemic viral infection can influence an established H. felis infection.